Zika Virus Infection Produces a Reduction on Aedes aegypti Lifespan but No Effects on Mosquito Fecundity and Oviposition Success - da Silveira, Isabella Dias; Petersen, Martha Thieme; Sylvestre, Gabriel; Garcia, Gabriela Azambuja; David, Mariana Rocha; Pavan, Márcio Galvão; Maciel-de-Freitas, Rafael (Frontiers in Microbiology, 2018)
America`s Pandemic of Zika virus (ZIKV) started soon after the first autochthonous cases in Latin America. Although Aedes aegypti is pointed as the primary vector in Latin America, little is known about the fitness cost due to ZIKV infection. We investigated the effects of ZIKV infection on the life-history traits of Ae. aegypti females collected in three districts of Rio de Janeiro, Brazil (Barra, Deodoro and Porto), equidistant ~25Km each other. Aedes aegypti mosquitoes were classified as infected (a single oral challenge with ZIKV) and superinfected (two ZIKV-infected blood meals spaced by 7 days each other). ZIKV-infection reduced Ae. aegypti survival in two of the three populations tested, and superinfection produced a sharper increase in mortality in one of those populations. We hypothesized higher mortality with the presence of more ZIKV-copies in Ae. aegypti females from Porto. The number of eggs laid per clutch was statistically similar between vector populations and infected and uninfected mosquitoes. Infection by ZIKV not produced effects on female oviposition success. ZIKV-infection affected Ae. aegypti vectorial capacity by reducing its lifespan although female fecundity remained unaltered. The outcome of these findings to disease transmission intensity still needs further evaluation.